2021
DOI: 10.1088/1742-6596/1828/1/012056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Fusion of Electromyographic and Electroencephalographic Data towards Use in Robotic Prosthesis Control

Abstract: We demonstrate improved performance in the classification of bioelectric data for use in systems such as robotic prosthesis control, by data fusion using low-cost electromyography (EMG) and electroencephalography (EEG) devices. Prosthetic limbs are typically controlled through EMG, and whilst there is a wealth of research into the use of EEG as part of a brain-computer interface (BCI) the cost of EEG equipment commonly prevents this approach from being adopted outside the lab. This study demonstrates as a proo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Workers from Aston University have recently reported encouraging results by combining EMG with EEG data sets as shown in Figure 4 (Pritchard et al, 2021). EMG signals were obtained from a Thalmic Labs' Myo armband, a low-cost EMG device with eight sensing electrodes, located on the subject's forearm (Figure 5).…”
Section: Brain-computer Interface Developmentsmentioning
confidence: 99%
“…Workers from Aston University have recently reported encouraging results by combining EMG with EEG data sets as shown in Figure 4 (Pritchard et al, 2021). EMG signals were obtained from a Thalmic Labs' Myo armband, a low-cost EMG device with eight sensing electrodes, located on the subject's forearm (Figure 5).…”
Section: Brain-computer Interface Developmentsmentioning
confidence: 99%
“…RAIN computer interface (BCI) is a technology that establishes a communication system between the human brain and external devices [1]. It has been applied in many fields, such as stroke rehabilitation [2,3], prosthetic control [4], quadcopter control [5], speech synthesis [6], and emotion recognition [7]. The techniques aiming to reconstruct hand motor function have been extensively studied [8][9][10] and are expected to enable rehabilitation training for stroke patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tortora et al proposed and evaluated a hybrid HMI to decode walking phases of both legs from the Bayesian fusion of EEG and EMG signals; the results showed that the fusion of EEG and EMG information helps keep a stable recognition rate of each gait phase of more than 80% independently on the permanent level of EMG degradation (Tortora et al, 2020). Using low-cost sEMG and EEG devices in tandem can achieve high accuracy with decision-level fusion, which reported accuracies of up to 99% (Pritchard et al, 2021). So, the fusion of EEG and sEMG can keep a stable recognition rate of tasks with high accuracy.…”
Section: Introductionmentioning
confidence: 99%